Efficiency Analysis for Plate Type Heat Exchangers Using Nanofluids in the Primary Cooling System of the TRIGA 2000 Nuclear Reactor with Computational Fluid Dynamics Code - Yusuf, Yusuf; Ramadhan, Anwar Ilmar; Umar, Efrizon; Fitriana, Rian; Firmansyah, Firmansyah; Azmi, Wan Hamzah (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
The TRIGA reactor is equipped with a primary cooling system that transfers heat from the reactor tank water to the secondary cooling system. Heat transfer in this system occurs mainly in plate-type heat exchangers located in the reactor building, using forced convection with the help of primary and secondary pumps. This research aims to evaluate the effectiveness, efficiency, heat transfer rate, and temperature difference. The analysis was carried out through CFD (Computational Fluid Dynamics) modeling using ANSYS Spaceclaim for geometric design and ANSYS FLUENT for simulation. Simulations using ZrO2-Water Nanofluid with volume concentrations of 0.2%, 0.6%, and 1% and variations in mass flow rates of 15 kg/s, 20 kg/s, and 25 kg/s. The simulation results show the distribution of temperature, pressure and fluid velocity. The theoretical analysis of the plate type heat exchanger shows that the use of ZrO2 with a concentration of 1% has the highest efficiency, which is 3.39% at a mass flow rate of 25 kg/s, and an efficiency of 64.82% at a mass flow rate. as much as 15 kg/s.